2013
DOI: 10.1002/jip.1408
|View full text |Cite
|
Sign up to set email alerts
|

Victim Gender, Number of Perpetrators, and Interpersonal Interaction in Stranger Rape: An Analysis of Direct and Moderator Effects

Abstract: This study examined the direct and moderator effects of number of perpetrators and gender of victim on interpersonal behaviour in stranger rape. Crime scene behaviours representative of hostility, involvement, control, and offender penetration in rape were examined for 496 UK, police‐recorded cases of stranger rape. Cases were grouped according to victim gender (male or female) and number of perpetrators (lone or multiple). This resulted in four groups (lone female, lone male, multiple female, and multiple mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The number of victims was not statistically significant, and may not be directly affected by use of substances prior to committing crimes. Perhaps, this relationship may be better explained by an indirect association through other factors such as access, supervision, level of planning, or violence (Hackett, Phillips, Masson, & Balfe, 2013; Lundrigan, 2014). However, the results revealed that substance use prior to the commission of sexual crimes was associated with sexual deviance.…”
Section: Discussionmentioning
confidence: 99%
“…The number of victims was not statistically significant, and may not be directly affected by use of substances prior to committing crimes. Perhaps, this relationship may be better explained by an indirect association through other factors such as access, supervision, level of planning, or violence (Hackett, Phillips, Masson, & Balfe, 2013; Lundrigan, 2014). However, the results revealed that substance use prior to the commission of sexual crimes was associated with sexual deviance.…”
Section: Discussionmentioning
confidence: 99%
“…This was lower than some previous research that suggested that in more than half of male rape cases force and physical injury was described (e.g., Walker et al, 2005 ). Moreover, a subsequent study by Lundrigan (2014) indicated that male victims were more likely than female victims to experience overtly hostile interactions. In addition, Ioannou et al (2017) argued that “most male-on-male sexual assaults are violent in nature” (p. 189).…”
Section: Grievance and Sexual Violence Beyond Male Rape Of Femalesmentioning
confidence: 99%
“…Peritraumatic schemas may be an additional mechanism Lauricella et al NP2053 that explains the relationship between sexual trauma and PTSS, but this has not been examined. Additionally, although there is literature discussing the importance of the relationship between the victim and the perpetrator on the resulting outcomes, the conclusions are mixed (Lundrigan, 2014;Temple et al, 2007;Ullman & Siegel, 1993). Clarifying the role of peritraumatic schemas and how they may depend on the victim-perpetrator relationship can help to understand the various factors that impact the development of PTSS because of sexual trauma.…”
Section: The Present Studymentioning
confidence: 99%
“…In addition to a lack of knowledge regarding the association of peritraumatic schemas and PTSS, understanding how the victim-perpetrator relationship impacts this association is also lacking. Evidence exists that the victim-perpetrator relationship is important to the sequelae of sexual trauma NP2050 Journal of Interpersonal Violence 38(1-2) (Lundrigan, 2014;Temple et al, 2007;Ullman & Siegel, 1993). It is also possible that the victim-perpetrator relationship is associated with the peritraumatic schemas experienced by the victim, meaning the beliefs the victim has about themselves, others, and the world may vary during sexual trauma depending on their relationship with the perpetrator.…”
mentioning
confidence: 99%